INSUFFICIENT CONSUMER PROTECTION IN E-COMMERCE UNDER INDONESIAN LEGAL SYSTEM - Rotinsulu, Jeannie Connie (LEX ET SOCIETATIS, 2021)
Despite relevant laws and regulations being in force for years, it has been argued that Indonesian legal system is not sufficient to protect consumers on e-commerce transactions. This article seeks to prove this premise by demonstrating insufficiency of Indonesian Consumer Law and  Electronic Information and Transaction Law as well as other relevant regulations  in addressing e-commerce issues on consumer protection.The Indonesian legal system does not adequately protect e-commerce consumers  particularly because of three main factors.  Firstly, the absence of the personal data protection law has been considered as to  be a significant issue of security measures on electronic commerce transactions.  Secondly,  it is attributed to the fact that the Consumer Protection Law has a little effect in enforcing rights of e-commerce users. Thirdly, the Electronic Information and Transaction Law and other relevant regulations that govern digital information and electronic commerce grant insufficient legal protection effect for on-line consumers. Significant consumer rights of privacy, security of on-line property, secure on-line payments platform, accuracy information and accessibility have not been protected effectively. The Law also tends to be used as to address the violation of distribution of electronic information and rights to freedom of expression issues.  The universal model law of UNCITRAL and the OECD guidelines  for consumer protection and personal data protection in e-commerce may be embraced to improve the protection of e-commerce users in Indonesia..Keywords: Consumer Protection, E-Commerce, Indonesia Legal system